Mimetic peptide AC2-26 of annexin A1 as a potential therapeutic agent to treat COPD - Possebon, Lucas [UNESP]; Costa, Sara S. [UNESP]; Souza, Helena R. [UNESP]; Azevedo, Lucas R. [UNESP]; Sant'Ana, Monielle; Iyomasa-Pilon, Melina M.; Oliani, Sonia M. [UNESP]; Girol, Ana Paula [UNESP] (Elsevier, 2018)
Chronic obstructive pulmonary disease (COPD) is related to inflammatory process caused by smoking habit. In this scenario, the anti-inflammatory protein Annexin A1 (AnxA1) may represent a therapeutic alternative. We performed experiments to evaluate the effects of the AnxA1 mimetic peptide Ac2-26 in an initial COPD model by physiological, histopathological, biochemical and immunohistochemical analyses. Weight loss, increased blood pressure, reductions in the pulmonary frequency and ventilation, loss of tracheal cilia, enlargement of the pulmonary intra-alveolar spaces and lymphoid tissue found in untreated smoke-exposed group were attenuated by AnxA1 peptide treatment. The Ac2-26 administration also protected against leukocytes influx in bronchoalveolar lavage (BAL), lung and trachea, and it also led to decreased hemoglobin, glucose, cholesterol, gamma glutamyl transferase and aspartato aminotransferase levels. Similarly, reduction of proinflammatory mediators and higher concentration of anti-inflammatory cytokine were found in macerated lung supernatant, blood plasma and BAL in the treated animals. Besides Ac2-26 group showed reduced tissue expressions of AnxA1, cyclooxygenase-2 and metalloproteinase-9, but formylated peptide receptor 2 (FPR2) overexpression. Our results all together highlighted the protective role of the Ac2-26 mimetic peptide in COPD with promising perspectives.
Keywords: Annexin A1; BAL; COPD; FPR2; Inflammation